2017
DOI: 10.1016/j.jelekin.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between external knee moments and muscle co-activation in subjects with medial knee osteoarthritis

Abstract: The relationship between external knee moments and muscle coactivation in subjects with medial knee osteoarthritis Selistre, LFA, Mattiello, SM, Nakagawa, TN, Gonçalves, GH, Petrella, M and Jones, R This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The medial and lateral malleoli, femoral epicondyles, seventh cervical vertebrae, greater trochanters, and acromia were removed after the static standing calibration trial was performed. These markers were used to construct the anatomical coordinate system for the trunk, pelvis, thigh, shank, and foot segments (Jones, Chapman, Parkes, Forsythe, & Felson, ; Selistre et al, ). The angular motion of all assessed joints was defined using Cardan angles in accordance with the recommendations of the International Society of Biomechanics (Wu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The medial and lateral malleoli, femoral epicondyles, seventh cervical vertebrae, greater trochanters, and acromia were removed after the static standing calibration trial was performed. These markers were used to construct the anatomical coordinate system for the trunk, pelvis, thigh, shank, and foot segments (Jones, Chapman, Parkes, Forsythe, & Felson, ; Selistre et al, ). The angular motion of all assessed joints was defined using Cardan angles in accordance with the recommendations of the International Society of Biomechanics (Wu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For each subject, a static calibration trial followed by five successful trials were collected for kinetic and kinematic analysis. The following reflective markers were located on anatomical landmarks bilaterally 49,50 : sternal notch, spinous process of C7, acromion, iliac crests, anterior and posterior superior iliac spines, greater trochanters of the femur, medial and lateral femoral epicondyles, medial and lateral malleoli, first, second and fifth metatarsal heads, base of the fifth metatarsal, and calcaneus. Four clusters built with 4 noncollinear markers were placed over the lateral side of thighs and shanks.…”
Section: Independent Variablesmentioning
confidence: 99%
“…While harnessing the entire data base to systematize more definitive trends than is evident in the present snapshot of current research may be valuable, it is the author's belief that more efforts towards developing carefully construed biomechanical, radiological, molecular, biochemical, and neuromuscular oriented prospective studies of adequate duration are indicated to advance this line of inquiry, despite the increasing volume of reports. To verify or dispute hypothetical evidence based associations depicted in Figure 1 and expand upon trends depicted in Table 2, more prospective studies focusing on muscle co-activation effects [17], the role of eccentric as well as concentric forces on the emergence and progression of osteoarthritic joint disease [40], as well as the role of distant muscles [42,69], and the tendon-aponeurosis complex [46] are indicated [46,59]. In addition, delineating the role of muscle fat infiltration [33,81], muscle inflammation [25], and vitamin D [30] and its impact on muscle structure and function in the context of osteoarthritis may…”
Section: Implications and Conclusionmentioning
confidence: 92%
“…14,15]. Yet others focused on examining the association between the impact of muscle co-activation processes on joint moments [16,17], sarcopenia and its relationship with osteoarthritis [18], muscle activation imbalances [19], the role of abnormal muscle loading forces [20], and muscle weakness and movement patterns [21] in the context of osteoarthritis.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation